4(2-t)=t-2

Simple and best practice solution for 4(2-t)=t-2 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(2-t)=t-2 equation:


Simplifying
4(2 + -1t) = t + -2
(2 * 4 + -1t * 4) = t + -2
(8 + -4t) = t + -2

Reorder the terms:
8 + -4t = -2 + t

Solving
8 + -4t = -2 + t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-1t' to each side of the equation.
8 + -4t + -1t = -2 + t + -1t

Combine like terms: -4t + -1t = -5t
8 + -5t = -2 + t + -1t

Combine like terms: t + -1t = 0
8 + -5t = -2 + 0
8 + -5t = -2

Add '-8' to each side of the equation.
8 + -8 + -5t = -2 + -8

Combine like terms: 8 + -8 = 0
0 + -5t = -2 + -8
-5t = -2 + -8

Combine like terms: -2 + -8 = -10
-5t = -10

Divide each side by '-5'.
t = 2

Simplifying
t = 2

See similar equations:

| 4x-17=(3x+11) | | 3+4x=-3x+6 | | -4-X+1-(4-1)=-2-X(4) | | 9=-2+y | | (6p+5)=18+15 | | 4(m-5)=2(m+3)+4 | | 3n+5-2n=-2 | | -8n=-40 | | 3t^2-16t+26=0 | | 6/5(5k+2)=-36 | | 2x+40(5x)=360 | | 2(x+8)=14x | | -6(1+4n)=-6n+6(n-9) | | h(-4)=7-2(-4) | | 4x+17=180 | | d/3.2=48 | | 2x-20i=8-4yi | | 5(2q+4)=2(4q-6) | | -6x+30=3(x-5) | | g(-4)=5(-4) | | 345=562.5-7.5x | | 4x(7)=70 | | 6/5(5k+2)=36 | | 4x-17+(3x+11)=180 | | 3+x/2=7 | | Y=-0.1x^2+6x+120 | | 4b+16+3b=46 | | pr=qs | | -21x^2+44x-15= | | 3x+5y-2z=22 | | 2(3m-4)=5(m+7) | | 12=10c |

Equations solver categories